Contextualising the Perceptions of Pharmacists Practicing Clinical Pharmacy in South Africa—Do We Practice what We Preach? - Bronkhorst, Elmien; Schellack, Natalie; Gous, Andries G. S. (Frontiers in Pharmacology, 2021)
The National Department of Health published their Quality Standards for Healthcare Establishments in South Africa and introduced the National Health Insurance, with the pilot phase that commenced in 2012. The system requires an adequate supply of pharmaceutical personnel and the direct involvement of clinical pharmacists throughout the medication-use process to ensure continuity of care, minimised risk with increasing improvement of patient outcomes. The study aimed to provide insight into the pressing issues of clinical pharmacy practice in South Africa, and sets out to contextualise the current profile of the pharmacist performing clinical functions. The study used a quantitative, explorative, cross-sectional design. The population included pharmacists from private and public tertiary hospitals. A questionnaire was administered, using Typeform™. Ethics approval was obtained from Sefako Makgatho Health Sciences University, National Department of Health and Private Healthcare groups. Categorical data were summarised using frequency counts and percentages; continuous data were summarised by mean values and standard deviations. The sample size included 70 pharmacists practicing clinical pharmacy (private sector n=59; public sector n=11). Most participants hold a BPharm degree (busy with MPharm qualification) (64%; n=70). No statistical significance was found between participants in private and public practice. Most pharmacist agreed (32% (private); n=59) and strongly agreed (45% (public); n=11) to have sufficient training to perform pharmaceutical care. The majority respondents felt that interventions made by the pharmacist improved the rational use of medicine (47% (private); 55% (public). Pharmacist interventions influence prescribing patterns (42% (private); 64% (public); and reduce polypharmacy (41% (private); 55% (public). The clinical functions mostly performed were evaluation of prescriptions (private 90%; public 82%), while the top logistical function is daily ordering of medication (40.7%; private), and checking of ward stock (36%; public). Although not all pharmacists appointed in South Africa has completed the MPharm degree in clinical pharmacy, the pharmacists at ward level perform numerous clinical functions, even if only for a small part of their workday. This paper sets the way to standardise practices of clinical pharmacy in South Africa, with a reflection on the differences in practice in different institutions